CRISIS MANAGEMENT AND PROJECT APPROACH - Т. V. Yurieva (Real Economics Publishing House, 2014)
The development of the new economy in terms of strategic changes may be accompanied by the appearance the unstable and crisis situations. These can be effectively controlled through the use of crisis management mechanism and project management methods. This approach allows developing and implementing of anti-crisis strategy, to obtain the necessary economic results in conditions of limited parameters (resources, time, etc.).